2018
DOI: 10.1002/mrm.27564
|View full text |Cite
|
Sign up to set email alerts
|

Echo time‐range effects on gradient‐echo based myelin water fraction mapping at 3T

Abstract: Purpose To investigate the effect of the range of TE on multi‐echo gradient echo–based myelin water fraction (MWF) mapping at 3 T. Methods Myelin water fraction estimation was performed using 3 widely used models: magnitude multipool, magnitude 3‐pool, and complex 3‐pool model. Simulations were conducted using a hollow cylinder model with susceptibility anisotropy. The TE range was varied, and its effect on MWF estimation was observed. The same analysis was also performed with in vivo data from 4 healthy volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 40 publications
(135 reference statements)
0
19
0
Order By: Relevance
“…In this approach, the initial values and bounds of the fitting parameters need to be set to avoid getting trapped in local minima (e.g. see [21]).…”
Section: A Model-based Mwf Mappingmentioning
confidence: 99%
“…In this approach, the initial values and bounds of the fitting parameters need to be set to avoid getting trapped in local minima (e.g. see [21]).…”
Section: A Model-based Mwf Mappingmentioning
confidence: 99%
“…Hence, the restricted number of water pools may hamper the use of ANNs by not reflecting the detailed aspects of practical changes occurring in tissues 9,37,38 . However, in previous studies, the three‐pool exponential model showed improved performance on MWF estimation using mGRE acquisitions 8,26,39 . Moreover, because of the increased sensitivity to physiological noise 11 and field inhomogeneities 13 in mGRE acquisitions, multicompartment model application with separable T2 amplitudes and frequency offsets for an unknown number of water pools might be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…9,37,38 However, in previous studies, the three-pool exponential model showed improved performance on MWF estimation using mGRE acquisitions. 8,26,39 Moreover, because of the increased sensitivity to physiological noise 11 and field inhomogeneities 13 in mGRE acquisitions, multicompartment model application with separable T * 2 amplitudes and frequency offsets for an unknown number of water pools might be challenging. Thus, only the three-pool exponential model was considered in this study, although different signal models could be adopted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations